Mapping Contextual Aspects that Influences Women in Computing in Latin America - Drummond, Bárbara (2023)
In light of the already acknowledged underrepresentation of women in Computing, the ongoing project “Latin American Open Data for Gender Equality Policies Focusing on Leadership in STEM” aims to support the implementation of institutional policies to promote gender equality in STEM. Activity 4 of this project involves mapping 1the factors, actors and policies that influence the career development and leadership of women in STEM, as well as collecting and analyzing this data. To explore these factors, both a systematic mapping study and a grey literature mapping were conducted. The results encompass 8 types of contextual factors and 196 sub-factors. Some competency questions were also raised, providing valuable data for future steps.